Disturbing the Divide: Poetry as Improvisation to Disorder Power Relationships in Research Supervision. (January 2015) - Fitzpatrick, Esther; Fitzpatrick, Katie
In this article, we share our use of poetry as a research supervision tool. We are not only colleagues but are also in a student–supervisor relationship. Early on in the PhD process, we began writing poems to each other on email as a way of communicating aspects of our research ideas that we felt were not able to be expressed in prose. We found that this use of poetry enabled a direct emotional engagement with the work and ideas we were forming. At the same time, we shaped our writing activities as a form of resistance, indulging in a form of anti-neoliberal critique. Crucially, however, we found that poetry also allowed us to form a closer relationship because it required both of us to be open and vulnerable. We didn't allow time to write and edit the poems but emailed them as soon as they were written.